From aboriginality to governmentality : the meaning of section 35(1) and the power of legal discourse - Hannigan, David (Allard Research Commons, 2009)
This thesis examines recent doctrinal developments regarding the aboriginal and treaty rights which are recognised and affirmed in s.35(l) of the Constitution Act, 1982. Specifically, it explores how the meaning of such rights is being constituted by diverse relations of power operating within specific 'cites' of struggle. Chapter I is a brief introduction to recent transformations in the legal discourse of the Supreme Court and an overview of the methodologies being employed in this thesis. In this regard, the author undertakes an interdisciplinary approach to discourse analysis. Chapter II draws upon the writings of Michel Foucault to make the argument for the analytical framework being utilised; namely, the study of 'law' within a 'sovereign- discipline- government' society. Chapter III examines the relationship between the productive power of the disciplines and the legal discourse constituting the content of aboriginal rights; the purpose being to explore to what extent law 'operates as a norm' within this area. Additionally, it provides a lead into the discussion of 'government' by outlining the rationality underpinning the test for the justified governmental infringement of aboriginal and treaty rights. Chapter IV, examines the relationship between the regulatory power of 'government' and the legal discourse around current treaty negotiations. Specifically, it explores the inter-dependency between rationalities of self-government and the governmental technologies associated with 'advanced' liberalism. In doing so, it focuses on an emerging treaty from British Columbia to assess the extent to which law is being used as 'a tactic of government'. Chapter V, examines the relationship between the deductive power of 'sovereignty' and the legal discourse constituting the content of Aboriginal title. It argues that recent developments require the Court to deal with the issue of legal pluralism. And to do so, in a way that lays a more successful foundation in law for the legitimate reconciling of the pre-existence of First Nations societies and the sovereignty of the Crown. Chapter VI provides some concluding comments about the insights gained from the proceeding analysis. In doing so, it offers a brief discussion of how the proceeding specific analysis may relate to some recent work in post-colonial studies.